Chemistry and antioxidant properties of essential oil and oleoresins extracted from the seeds of tomer (Zanthoxylum armatum DC) - Singh, Gurdip (2013)
The seeds of Zanthoxylum armatum DC, on hydrodistillation, yielded 1.2% of the essential oil. The oleoresins were extracted by a Soxhlet extractor using ethanol, ethyl acetate, and isopropyl alcohol. Gas chromatography-mass spectrometry analysis of the essential oil resulted in the identification of 38 components, of which linalool (62%) and limonene (18.1%) were the major components. The major components of oleoresins were linoleic acid, palmitoleic acid, and linalool. The antioxidant potential of essential oil and oleoresins were evaluated by 2,2-diphenyl picrylhydrazyl radical scavenging, Fe 2+ chelating, ferric thiocyanate method, and various lipid peroxidation assays. The essential oil showed maximum antioxidant potential, whereas oleoresins showed moderate antioxidant activity. *This article is part 73 in a series on essential oils.